John Burroughs papers - Burroughs, John, 1837-1921.
Chiefly correspondence between Burroughs and Albert H. Pratt, president of the Burroughs Nature Club. Also, fair copy of Burroughs' poem "Waiting," photocopy of "Bobolink," and galley sheets for "Notes on Walt Whitman as Poet and Person."
Photocopy produced from originals with the permission of W.W. Boyd.
Naturalist, author, and poet.
Collection material in English.
Keywords: Poetry; Pratt, Albert H. -- Correspondence; Whitman, Walt, -- 1819-1892.; Burroughs Nature Club (U.S.); Authors; Naturalists; Poets